2013
DOI: 10.1021/sb400010m
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrea jecorina Cellobiohydrolase I Stabilizing Mutations Identified Using Noncontiguous Recombination

Abstract: Noncontiguous recombination (NCR) is a method to identify pieces of structure that can be swapped among homologous proteins to create new, chimeric proteins. These “blocks” are encoded by elements of sequence that are not necessarily contiguous along the polypeptide chain. We used NCR to design a library in which blocks of structure from Hypocrea jecorina cellobiohydrolase I (Cel7A) and its two thermostable homologues from Talaromyces emersonii and Chaetomium thermophilum are shuffled to create 531,438 possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Although these studies demonstrate that GH7 enzyme thermal stability can be improved through a variety of protein engineering approaches, we do not yet understand why these mutations, either singular or multiple, result in improved stability. Moreover, there has only been one report of improved thermal stability of H. jecorina Cel7A in the scientific literature (41).…”
mentioning
confidence: 99%
“…Although these studies demonstrate that GH7 enzyme thermal stability can be improved through a variety of protein engineering approaches, we do not yet understand why these mutations, either singular or multiple, result in improved stability. Moreover, there has only been one report of improved thermal stability of H. jecorina Cel7A in the scientific literature (41).…”
mentioning
confidence: 99%
“…This suggests that each sequence/structural block behaves differently in different contexts. For certain soluble protein properties (e.g., thermostability), it has been shown that block contributions are additive, that is, context independent, and that chimera stability can be predicted using linear regression (28,29,49,50). Our data suggest that ChR localization and photocurrent properties, however, require a more complex model to account for the nonlinear dependence of function on block sequence.…”
Section: Resultsmentioning
confidence: 80%
“…StickWRLD has been used previously to detect interpositional dependencies (IPDs) between residues in both DNA 3 and protein [15][16][17] alignments.…”
Section: Representative Resultsmentioning
confidence: 99%
“…It has long been known that not all point mutations toward consensus provide improved stability or activity. More recently, proteins designed to take advantage of known IPDs in their sequence have been shown to result in greater activity than the same protein designed strictly from consensus 1,2 (manuscript in preparation), similar to the idea of stabilizing point mutations 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation